Pengaruh Media Sosial Terhadap Tanggung Jawab Moral Mahasiswa Gizi Universitas Negeri Medan - Ade Siti Aprila; Ahmad Baihaqi; Meriska Sembiring; Qarina Yustiviola; Riznaya Zahra Azila (LPPM Politeknik Pratama, 2023)
Researchers want to conduct a more in-depth descriptive analysis study regarding the Influence of Social Media on Moral Responsibility in Students of the UNIMED Nutrition Study Program Class of 2022. The aim and benefits of this research are to determine the use of social media to fulfill the responsibilities of Nutrition Students Class of 2022 with their identity. as a student. This research uses qualitative methods with case studies. This research focuses in depth on a particular subject and studies it as a case. The research subject selection technique uses purposive sampling technique. The data collection techniques used in this research are interviews, observation and documentation. This research uses data triangulation as a technique to measure the validity of the data. Based on the results of research that has been conducted, it shows that social media has great potential to influence students' moral responsibilities, both positively and negatively. Students need to realize this potential and use social media wisely and responsibly. In this way, students can become agents of positive change in society. By using social media wisely and responsibly, students can become agents of positive change in society. Students can use social media to promote tolerance, justice, and equality. Students can also use social media to educate people about social issues and to encourage them to take action.